IMPLEMENTASI SAFETY TALK SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA DI STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) KOTA BARU JAMBI - Atahya Nasyawa Islami; Usi Lanita; Budi Aswin (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
Background: Workplace accidents remain a major occupational health and safety concern, including at gas stations (SPBU), mainly due to unsafe behaviors and hazardous working conditions. Safety talks are an important OHS communication strategy to prevent workplace accidents. This study aimed to analyze the implementation of safety talks as an accident prevention effort at gas stations in Jambi City in 2026. Methods: A qualitative study with an analytical approach was conducted through in-depth interviews and observations involving eight informants, including managers, supervisors, and operators. Results: The findings indicated that safety talks were generally implemented effectively in terms of implementer qualifications, methods, types, and duration. Psychosocial factors, particularly work demands and coworker support, also influenced implementation effectiveness. Safety talks improved workers’ understanding of occupational hazards and promoted safer work practices. Conclusion: Safety talks contribute significantly to workplace accident prevention; however, greater consistency, supervision, and worker participation are needed to optimize their effectiveness.